Upaya Meningkatkan Hasil Belajar Matematika dengan Menggunakan Metode Demonstrasi Pada Kelas II di SDN - Santy, Maria; Supriyanto Manurung , Alberth (Pusdikra-Publishing.com, 2025)
This research comes from observations at SD Negeri Setia Asih 05, where it was found that students tended to enjoy learning more on their own or showed less interest in Mathematics lessons delivered through the lecture method. Meanwhile, one useful learning method is the demonstration method. This method can help engage students in learning so that they do not feel stuck or bored. With this method, students can see the teaching aids shown during the learning session. The aim of this research is to improve the learning outcomes of class II students at SDN Setia Asih 05. This research was conducted in the form of classroom action research (PTK) by utilizing data collection techniques through observation, examiners and interviews. Increase in student learning outcomes from the pre test by 72% to 84%. With an increase of 12%. After that, in their activities, the percentage of teacher participation increased from 83% to 84%. This had an impact on increasing student participation from 65% to 83%, an increase of 18%.